The life and piano works of Alexander Tikhonovich Gretchaninoff (1864-1956) - Galentine, Shane Nelson (Kansas State University, 2013)
Alexander Tikhonovich Gretchaninoff (1864-1956) was a prolific composer from Russia’s Romantic age who explored the art of musical writing within an extensive number of genres and forms and showed an unusually strong interest in the creation of solo piano pieces for and about children. It is important that musicians in general and pianists in particular investigate his compositions and gain an understanding of their nature and potential usefulness as teaching pieces and as works worthy of public performance. My research consisted of an examination of Gretchaninoff’s autobiography, the study of numerous secondary accounts of his life and personal analysis of piano scores written by the master. My investigation uncovered the almost hidden existence of a large number of attractive musical works which Gretchaninoff wrote for solo piano as well as insightful details concerning the circumstances and motives that inspired the master to compose within the parameters of this genre. The following pieces are performed as part of this presentation: (from Children’s Album, Op. 98) A Tale, In the Camp of the Lead Soldiers, Lead Soldiers on the March, Hobby-Horse, Nurse Is Sick, Lullaby, Little Dance, Dreadful Event, After the Ball, On a Travel Tour, The Little Would-be Hero; (from 12 Little Sketches for Children, Op. 182) Sunrise, With the Fishing Rod, On the Swing, A Country Lad; (from A Child’s Day, Op. 109) Morning Prayer, The Broken Toy, The Happy Return Home; (from The Grandfather’s Book, Op. 119) My Dear Mommy, Swallow Dance, Pussy Is Ill, On the Swing; (from Glass Beads, Op. 123) Morning Promenade, On a Bicycle, Difficult Work; (from Andrusha’s Album, Op. 133) The Dance of the Gold Fishes, My Little Dog Joujou; (from Album Leaves, Op. 139) After Walking; (from Nina’s Album, Op. 141) After Mass, Dreaming, At the Wheel; (from Arabesques, opus number in dispute) Russian Folksong, A Sad Little Story; Sonatina in F major, Op. 110, #2 – 1. Allegro giocoso, 2. Menuet (Moderato grazioso) and Trio, 3. Finale – Allegro.
Keywords: Alexander Gretchaninoff; Children's piano pieces; Russian romantic composers; Russian folk music; Russian Orthodox Church choral works; Romantic Russian piano pieces; Music Education (0522)